Total synthesis of bioactive canthine alkaloid cordatanine comprising in situ double oxidative aromatization of tetrahydrocarbazole - Shelar, S. V.; N. P. Argade (ACS Omega, 2017)
Starting from tryptamine and methoxymaleic anhydride, concise and efficient total synthesis of cordatanine has been accomplished via regioselective reduction of methoxymaleimide, acid-catalyzed intramolecular cyclization of the formed lactamol, in situ stepwise oxidations leading to aromatization, and intramolecular cyclization with the exchange of N-regioselectivity. An attempted synthesis of regioisomeric natural product zanthochilone has been described in brief with reversal of reduction selectivity.